3D LnIII-MOFs: displaying slow magnetic relaxation and highly sensitive luminescence sensing of alkylamines. Issue 4 (20th December 2018) - Huang, Hong; Gao, Wei; Zhang, Xiu-Mei; Zhou, Ai-Mei; Liu, Jie-Ping
Abstract : Six isomorphous Ln-based MOFs with 3D structures have been synthesized under solvothermal conditions. Dy-MOF (5 ) shows slow magnetic relaxation behaviors. Eu-MOF (3 ) can serve as a recyclable sensor towards alkylamines in water systems. Abstract : Six new 3D isomorphous lanthanide metal organic frameworks (Ln-MOFs), [Ln2 (L)2 (DMF)2 (H2 O)4 ]·H2 O·DMF (Ln = Pr (1 ); Sm (2 ); Eu (3 ); Gd (4 ); Dy (5 ); Ho (6 )); H3 L = 5-(2-nitro-4-carboxylphenyl)isophthalic acid, have been solvothermally synthesized and characterized. Crystallographic studies revealed that these MOFs were isomorphous 3D frameworks in which the dinuclear units with double (μ-COO)2 bridges were interlinked by the L ligands. They represent the (3, 6)-connected (4 2 ·6)(4 3 ·6 8 ·8 2 ·10·12) topology. The magnetic coupling through double carboxylate bridges is antiferromagnetic in Pr-MOF (1 ), Gd-MOF (4 ), Dy-MOF (5 ) and Ho-MOF (6 ). Furthermore, Dy-MOF (5 ) shows slow magnetic relaxation behaviors under zero dc field. The luminescence sensing experiments demonstrated that Eu-MOF (3 ) displayed highly selective, well-recyclable properties and a low detection limit for sensing alkylamines in water systems. The study of Ln-MOF sensing for alkylamines is very scarce.